2005
DOI: 10.1182/blood-2004-04-1309
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 regulates NF-κB recruitment to the IL-12p40 promoter in dendritic cells

Abstract: Interleukin-10-deficient (IL-10 IntroductionInterleukin-10-deficient (IL-10 Ϫ/Ϫ ) mice develop spontaneous T-helper 1 (Th-1)-mediated colitis when housed under specific pathogen-free (SPF) conditions. [1][2][3] In this experimental model, enhanced IL-12p40 production by immune cells represents a key feature of intestinal inflammation, as demonstrated by the prevention and partial treatment of colitis by anti-IL-12 antibodies. 4,5 This suggests that in absence of IL-10, the host mounts a dysregulated innate res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 53 publications
13
111
0
Order By: Relevance
“…with a previous finding showing higher LPS-induced IL-12p40 secretion in IL-10 Ϫ/Ϫ compared with IL-10 wt/wt mice (33). Importantly, E. faecalis/E.…”
Section: E Faecalis/e Coli Lysates Induced I B␣ Degradation and Il-supporting
confidence: 57%
See 1 more Smart Citation
“…with a previous finding showing higher LPS-induced IL-12p40 secretion in IL-10 Ϫ/Ϫ compared with IL-10 wt/wt mice (33). Importantly, E. faecalis/E.…”
Section: E Faecalis/e Coli Lysates Induced I B␣ Degradation and Il-supporting
confidence: 57%
“…BMDC were generated from the femur and tibia of IL-10 wt/wt ;NF-B EGFP , IL-10 Ϫ/Ϫ ;NF-B EGFP and IL-10 Ϫ/Ϫ ;MyD88 Ϫ/Ϫ mice as described previously (33). Bone marrow cells were flushed and depleted of RBC using RBC lysing buffer (Sigma-Aldrich), and then cultured in ultralow-adherence 24-well plates (Costar) in complete medium (RPMI 1640) supplemented with 10% FCS, 2 mM L-glutamine, 50 M 2-ME, 10 ng/ml murine rGM-CSF, and 10 ng/ml murine rIL-4 (both from PeproTech).…”
Section: Generation and Stimulation Of Bone Marrow-derived DC (Bmdc)mentioning
confidence: 99%
“…The ability of Stat3 to inhibit expression of similar immunostimulatory molecules in immune cells in tumor setting and in normal cells has also been demonstrated [4]. The underlying molecular mechanism(s) for downregulating Th1 immune responses remain fully unexplored, although it has been suggested that Stat3 has an antagonistic effect on immunostimulatory effects of NF-κB [11,12] and Stat1 [13], both of which are critical for inducing Th1 immune responses.…”
Section: Oncogenesis and Suppression Of Tumor Immunity: The Role Of Smentioning
confidence: 99%
“…These data suggest that CTLA4Fc exerts its regulatory effect downstream of the proximal NF-κB signaling pathway. STAT3 is a transcription factor that can modulate NF-κB binding to the IL-12p40 promoter [42] and negatively regulate LPS signaling [20]. IL-10 is a well-characterized STAT3 activator, which has been previously associated with Treg cell-DC crosstalk [43].…”
mentioning
confidence: 99%